Identity in the Literature of Czech Těšín Region - Střelec, Karel (Poznańskie Studia Slawistyczne, 2018)
The monograph called Identita v literatuře Těšínska (Identity in the Literature of Czech Těšín Region) deals with the works of the Polish national minority in this region, especially with the literature after the World War II. The author also deals with the reception of works by Czech and Polish authors and the translation activities of the Polish minority. Particular studies bring specific results of Martinek‘s expert research and give an inspiring reflection of the topic being discussed. The book thus adequately follows the author‘s earlier work on the literature of Těšínsko, especially on the works Identita v literatuře českého Těšínska. Vybrané problémy (Identity in the Literature of Czech Těšín Region. Chosen Problems), 2009, and Życie literackie na Zaolziu 1920–1989 (Literary Life at Zaolzie 1920–1989), 2008, and a number of other partial studies.